The ecotoxicity and social impacts of industrial pollution: Insights on intervention and bioremediation strategies in Africa - Gloria Ifeoma Ujuagu; Onome Ejeromedoghene; Peter Olusakin Oladoye; Charles Obinwanne Okoye; Yakubu Adekunle Alli; Mayowa Ezekiel Oladipo; Jintu Gu (Environmental Pollution and Management)
The integrity and functionality of the environmental system in Africa are seriously threatened by contaminants emerging from different industrial activities. This piece of work reveals that several activities from the agricultural, oil/gas, medical, and mining industries release tonnes of pollutants daily, which are indiscriminately discharged into different aspects of the environment, thereby polluting the ground and surface water, soil, and air. These activities have impacted human/animal health, leading to several illnesses, and caused ecosystem dysfunction, such as climate change, biodiversity loss, aquatic habitat alteration, and marine ecosystem contamination. In addition, advanced industrial activities have produced emerging contaminants from e-waste that have released enormous amounts of inorganic and organic pollutants. Herein, new insights into the socio-economic, socio-political, and ecotoxicity implications arising from the urbanization and industrial evolution in Africa have been highlighted. More importantly, research gaps covering novel interventions such as mass media campaigns, digital health services, as well as bioremediation strategies and predictive models based on machine learning approaches are suggestive measures that will help policy-makers, researchers, and governments of countries in Africa to manage/mitigate the industrial pollution crisis.